Afterdepolarizations and abnormal calcium handling in atrial myocytes with modulated SERCA uptake: a sensitivity analysis of calcium handling channels. (25th May 2020) - Lo, Andy C. Y.; Bai, Jieyun; Gladding, Patrick A.; Fedorov, Vadim V.; Zhao, Jichao
Abstract : Delayed afterdepolarizations (DADs) and spontaneous depolarizations (SDs) are typically triggered by spontaneous diastolic Ca 2+ release from the sarcoplasmic reticulum (SR) which is caused by an elevated SR Ca 2+ -ATPase (SERCA) uptake and dysfunctional ryanodine receptors. However, recent studies on the T-box transcription factor gene (TBX5) demonstrated that abnormal depolarizations could occur despite a reduced SERCA uptake. Similar findings have also been reported in experimental or clinical studies of diabetes and heart failure. To investigate the sensitivity of SERCA in the genesis of DADs/SDs as well as its dependence on other Ca 2+ handling channels, we performed systematic analyses using the Maleckar et al . model. Results showed that the modulation of SERCA alone cannot trigger abnormal depolarizations, but can instead affect the interdependency of other Ca 2+ handling channels in triggering DADs/SDs. Furthermore, we discovered the existence of a threshold value for the intracellular concentration of Ca 2+ ([Ca 2+ ]i ) for abnormal depolarizations, which is modulated by the maximum SERCA uptake and the concentration of Ca 2+ in the uptake and release compartments in the SR ([Ca 2+ ]up and [Ca 2+ ]rel ). For the first time, our modelling study reconciles different mechanisms of abnormal depolarizations in the setting of 'lone' AF, reduced TBX5, diabetes and heart failure, and may lead to more targeted treatment for these patients. This article is part of the theme issue 'Uncertainty quantification in cardiac and cardiovascular modelling and simulation'.